Selenium Nanoparticles in Folate-Targeted Delivery of the pCMV-Luc DNA Reporter Gene - Maiyo, Fiona C.; Mbatha, Londiwe S.; Singh, Moganavelli (Current Nanoscience, 2021)
Background: Selenium, an essential micronutrient, has been studied for decades for its anticancer properties. Selenium nanoparticles (SeNPs) have now emerged as an interesting alternative for drug and gene delivery. Aims: We aimed to demonstrate in proof of principle, the potential use of SeNPs in targeted pCMVLuc DNA (pDNA) delivery in vitro. Objective: To chemically synthesize, characterize and evaluate the transgene expression of functionalized SeNPs in five human cell lines. Methods: SeNPs were synthesized via chemical reduction, coated with chitosan (Ch) and a targeting moiety, folic acid (FA). All nanoparticles were characterized by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), UV-vis and Fourier transform infra-red (FTIR) spectroscopy. Nanoparticle:pDNA interactions were assessed using the electrophoretic mobility shift, dye displacement and nuclease protection assays. The MTT and Luciferase reporter gene assays were used to determine cytotoxicity and transgene expression, respectively, in the human colorectal adenocarcinoma (HT-29 and Caco-2), breast adenocarcinoma (MCF-7), oral epidermoid/cervical carcinoma contaminant (KB) and the embryonic kidney (HEK293) cells. Results: Homogenous nanoparticles of 60-70 nm were able to successfully bind, compact and protect the pDNA from enzyme digestion. Low cytotoxicity was observed in all cells, except for the MCF-7 cells, which could be attributed to apoptosis and necrosis. Luciferase gene expression was highest for the targeted nanocomplexes in the folate-receptor rich KB cell line, confirming nanocomplex uptake through folate receptor-mediated endocytosis. Conclusion: This study opens a new avenue for synergistic treatment of cancer, combining selenium’s bioactivity and its carrier potential for therapeutic gene delivery.
Keywords: Selenium nanoparticles